2013
DOI: 10.3851/imp2681
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cardiovascular Disease Risk Markers in HIV-Infected Patients Receiving Abacavir and Tenofovir: The Nucleoside Inflammation, Coagulation and Endothelial Function (Nice) Study

Abstract: Background The association between abacavir (ABC) and cardiovascular disease (CVD) risk in HIV-infected individuals is unclear. Putative mechanisms for an effect of ABC on CVD risk including endothelial dysfunction have been proposed; however, a biological mechanism has not been established. Methods This was a cross-sectional study of HIV-infected subjects with HIV RNA levels <400 copies/ml, who were randomly assigned to ABC or tenofovir (TDF) as initial therapy during a prior clinical trial. A small cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 27 publications
1
21
1
1
Order By: Relevance
“…51,52 However, evidence of an association of abacavir use with these biomarkers has not been consistent across studies. 53,54 More research is needed to establish the biological mechanism by which abacavir may increase CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 However, evidence of an association of abacavir use with these biomarkers has not been consistent across studies. 53,54 More research is needed to establish the biological mechanism by which abacavir may increase CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…A single center study of 61 treated and suppressed HIV-infected individuals found that those taking abacavir had lower FMD (75); however, a study of 148 individuals who initially were assigned randomly to abacavir or tenofovir did not find lower FMD among those taking abacavir. (76). …”
Section: Hiv and Cvd Riskmentioning
confidence: 99%
“…However, endothelial damage promotes the mobilization and recruitment of inflammatory cells to the vascular wall, and angiotensin II stimulates AT1R-mediated leukocyte-endothelial cell interactions. Although data are conflicting, 45,46 increasing evidence suggests that abacavir may contribute to endothelial dysfunction via increased leukocyte-endothelial cell interactions, 47,48 and we cannot rule out the possibility that this is mediated through interactions with the RAS. Additionally, abacavir may increase platelet activation by blunting the effect of nitric oxide on platelets, 49 and telmisartan-induced nitric oxide release could possibly overcome this effect of abacavir.…”
Section: Discussionmentioning
confidence: 87%